Evaluation of methods for rehabilitation of logged-over lowland forest in Pasoh, Negeri Sembilan, Malaysia - Maswar; Mokhtaruddin, A.M.; Majid, N.M.; Hanum, I.F.; Yusoff, M.K.; Azani, A.M.; Kobayashi, S. (Center for International Forestry Research, 2001)
Four rehabilitation methods were tested in logged-over lowland tropical forest in Pasoh Forest Reserve, Negeri Sembilan, Peninsular Malaysia. The treatments were: line planting (T1), gap planting 10m x 10m x 5 ha-1 (T2), gap planting 20 m x 20 m x 5 ha-1 (T3) and gap planting 10 m x 10 m x 9 ha-1 (T4). Hopea odorata, Azadirachta excelsa and Vitex pubescens were planted in the lines and gaps. One year after planting, percentage survival of seedlings were: 97%, 96%, 93% and 93% respectively for T1, T4, T2 and T3 for Hopea odorata; 96%, 90%, 88% and 85% respectively for T4, T1, T3 and T2 for Azadirachta excelsa; and 97%, 94%, 87% and 76% respectively for T4, T1, T3 and T2 for Vitex pubescens. The costs for each treatment per hectare were RM 2862; RM 1520; RM 684 and RM 380 for T1, T3, T4 and T2 respectively. In general soil properties (bulk density, organic matter, soil moisture and pH) before and after rehabilitation treatments were not significantly different suggesting all the rehabilitation methods can prevent soil degradation. Technically, line planting and gap planting methods were suitable for rehabilitation of this area but in terms of economic cost and effective area planted, gap planting was more efficient and effective than line planting. Hopea odorata, Azadirachta excelsa and Vitex pubescens are suitable for rehabilitation of this forest.